2020
DOI: 10.3389/fnins.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of the Effects of Gut Microbiota Composition on Neurotransmitter Metabolic Pathways in Children With Attention Deficit Hyperactivity Disorder

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is a neuropsychiatric condition that may be related to an imbalance of neural transmitters. The gut microbiota is the largest ecosystem in the human body, and the brain-gut axis theory proposes that the gut microbiome can affect brain function in multiple ways. The purpose of this study was to explore the gut microbiota in children with ADHD and assess the possible role of the gut microbiota in disease pathogenesis to open new avenues for ADHD treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
135
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(142 citation statements)
references
References 52 publications
7
135
0
Order By: Relevance
“…Notably, the reported distinct bacterial taxa between ADHD patients and HCs were highly inconsistent in previous studies [18][19][20][21][22][23]. The disturbed bacterial taxa in one cohort may never be replicated or may be opposite in abundance in another cohort.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Notably, the reported distinct bacterial taxa between ADHD patients and HCs were highly inconsistent in previous studies [18][19][20][21][22][23]. The disturbed bacterial taxa in one cohort may never be replicated or may be opposite in abundance in another cohort.…”
Section: Discussionmentioning
confidence: 75%
“…We found a significantly lower gene number in ADHD or C-ADHD patients than in HCs, though the gut microbiota richness, namely, alpha diversity, was similar between any two groups. There were also no significant differences in alpha diversity between ADHD patients and HCs in the Dutch [18] and Chinese (Zhejiang and Beijing) cohorts [19,23]. However, two other cohorts from Germany [20] and China (Taiwan) [21], showed reduced or increased alpha diversity in ADHD patients, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, there are some efforts to control neurological disorders by applying the gut-brain axis theory, a bidirectional communication between the brain and gastrointestinal tract [ 50 , 51 ]. In cases of ADHD, there is evidence demonstrating that gut microbiota affects brain neurodevelopment [ 52 , 53 , 54 , 55 ]. For instance, Szopinska-Tokov et al suggested that inattentive behavior that appeared in ADHD patients is associated with a specific bacterium [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the decreased abundance in Faecalibacterium spp. yielded also a negative correlation with ADHD severity scores (215,216). This genus is associated with anti-inflammatory skewing of immune responses and its decreased abundance is observed in allergies.…”
Section: Association With Specific Gut Microbiota Profilesmentioning
confidence: 92%
“…Next generation "shotgun" (metagenomic) sequencing has been applied to a small study of ADHD youth (216). Interestingly, pathway analyses of gene functional annotations revealed abnormalities of metabolic pathways associated with dopaminergic and serotonergic systems, consistent with their hypofunctionality.…”
Section: Association With Specific Gut Microbiota Profilesmentioning
confidence: 99%